DESIGNING AN ACCOUNTING SYSTEM USING MICROSOFT ACCESS APPLICATIONS AT TOKO J5 - Jefveny Kho; Edi Edi (Universitas Internasional Batam, 2022)
Toko J5 is a grocery store in Komplek Nagoya Point Blok J No 5. Toko J5 has been chosen as the partner in this study's implementation. The store currently lacks a strong accounting information system for recording business transactions so that it meets the criteria for implementing community service activities. Based on the issues discovered, an accounting information system was designed using Microsoft Access that may be used in the firm to assist in the recording of full transactions and the production of accurate financial reports. The resulting financial statements are in the form of statements of financial position, statements of profit or loss, statement of changes in equity, cashflow statements, general ledger, trial balance, inventory reports, accounts payable reports, accounts receivable reports, sales reports, purchase reports and depreciation report. The accounting information system is also capable of assisting business owners in precisely determining the financial status of their company and making the appropriate decisions.